Best Approximations of $q$-Ellipsoids in Spaces $S_{ϕ}^{p,μ}$ - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We find exact values of the best approximations and basic widths of $q$-ellipsoids in the spaces $S_{ϕ}^{p,μ}$ for $q > p > 0$.